Development Of A Transformer Oil Temperature And Pressure Monitoring System Using SCADA Labview With Blynk Interface - jauza, aura; Rozak , Ojak Abdul (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2026)
The increasing demand for electrical energy, driven by industrial growth and technological advancements, has made transformers critical components in power distribution systems, essential for maintaining supply quality. While transformers function to regulate voltage levels, they are susceptible to heat generation from current flow, making temperature monitoring crucial (must remain below 85°C per IEC 60076-2 standard) to prevent failures. This study aims to develop a real-time monitoring system for transformer oil temperature and pressure using SCADA LabVIEW integrated with a Blynk interface. The system employs 4-20mA temperature and pressure transmitters, a Modbus JY-DAM0222 module, a Modbus HF2211 gateway, and an ESP32 microcontroller for data acquisition and transmission. Test results demonstrate high system accuracy with average measurement errors of 0.11% for temperature and 0.02% for pressure. The LabVIEW-Blynk integration enables remote monitoring via mobile devices, allowing early detection of potential transformer faults. This system provides an effective solution to enhance transformer operational reliability in power distribution networks.